Agriculture and the rural economy of Pakistan: Issues, Outlooks, and Policy Priorities - Spielman, David J.; Malik, Sohail Jehangir; Dorosh, Paul A.; Ahmad, Nuzhat (2017)
IFPRI Book Launch Agriculture and the Rural Economy in Pakistan: Issues, Outlooks, and Policy Priorities